Synthesis and chemical composition analysis of protocatechualdehyde-based novel melanin dye by 15T FT-ICR: High dyeing performance on soft contact lens - Ahn, Soo Yeon; Choi, Mira; Jeong, Da woon; Park, Seo A.; Park, Hyun A.; Jang, Kyoung Soon; Choi, Kwon Young (Dyes and Pigments, 2019)
In this study, novel melanin pigments were prepared through the eco-friendly microbial conversion of caffeic acid by engineering Escherichia coli BL21(DE3) cells. The cells expressed feruloyl-CoA synthetase (FCS) and enoyl-CoA hydratase/aldolase (ECH) for the conversion of caffeic acid into protocatechualdehyde. The synthesized protocatechualdehyde further underwent oxidative modification into a diquinone structure, followed by polymerization into melanin complex (F/E-Melanin). The expression of FCS and ECH in the presence of 90 mg/L caffeic acid (0.5 mM) could produce F/E-Melanin black pigments up to 170 mg dry wt/L within 12 h. Interestingly, the synthesized melanin was applied for hydrogel of soft contact lens dyeing and showed excellent dyeing performance with biological activities of antibacterial and antioxidant capacities, as well as a higher water-content rate than those of the existing synthetic melanins prepared in this study. The synthesized F/E-Melanin polymers were structurally analyzed by 1H NMR and FT-IR. Interestingly, the molecular composition such as Van Krevelen plots with H/C and O/C ratio, double bond equivalents with carbon number, and CHONS distribution of the five synthetic melanins were characterized by interpreting data obtained from 15T FT-ICR mass spectrometry analysis.
Keywords: Caffeic acids; Chemical composition analysis; FT-ICR mass spectrometry; l-Tyrosine; Mass analysis; Microbial conversions; Molecular compositions; Oxidative modification; 15T-FT-ICR mass analysis; Caffeic acid; ECH; FCS; L-tyrosine; Melanin